Conflict Analysis and Work Environment on Employee Productivity at the PP-PA Office of South Sumatera Province - Valianti, Reva Maria; Hamzah, Syukri (Graduate Program Magister Manajemen Pendidikan, 2022)
The purpose of this study is 1) to determine the effect of the work environment on the work productivity of employees at the PP-PA Office of South Sumatera Province, 2) to determine the effect of work conflict on employee work productivity in the PP-PA Office of South Sumatera Province. And 3) to determine the effect of the work environment and work conflict on employee work productivity at the PP-PA Office of South Sumatera Province. The research method used is a descriptive method with a research sample of 48 ASN employees at the PP-PA Office of South Sumatera Province. Data analysis by questionnaire. The results of the study with indicators of work conflict, work environment, and employee productivity showed a good predicate with a magnitude of 79.64%. Our recommendation is to improve the work environment and prevent and handle work conflicts properly will increase employee productivity at the PP-PA Office of South Sumatera Province.